2020
DOI: 10.1177/2053434520981357
|View full text |Cite
|
Sign up to set email alerts
|

Costs, burden and quality of life associated with informal caregiving for children with Lymphoma attending a tertiary hospital in Ghana

Abstract: Introduction Primary family caregivers provide substantial support in the management of lymphoma, potentially affecting their quality of life and increasing household health care costs. Our aim was thus to determine the economic costs and quality of life of primary caregivers of children with lymphoma. Methods This cross-sectional study involved primary informal caregivers of children with lymphoma attending the pediatric cancer unit at Komfo Anokye Teaching Hospital. The study adopted a cost-of-illness approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 30 publications
(25 reference statements)
1
20
0
Order By: Relevance
“…A study in Ghana assessing medicines for treating childhood cancer estimated that it would cost on average $900 to treat a 30 kg child (4). In a cost-of-illness study, Dawson et al estimated an average cost of $440 for treating lymphoma in children (12). Similar to our nding, the average costs of treating Burkitt's Lymphoma in Uganda were estimated to be $1,350 (8).…”
Section: Discussionsupporting
confidence: 75%
“…A study in Ghana assessing medicines for treating childhood cancer estimated that it would cost on average $900 to treat a 30 kg child (4). In a cost-of-illness study, Dawson et al estimated an average cost of $440 for treating lymphoma in children (12). Similar to our nding, the average costs of treating Burkitt's Lymphoma in Uganda were estimated to be $1,350 (8).…”
Section: Discussionsupporting
confidence: 75%
“…Six studies from Southern Africa, Zimbabwe ( 29 ), Madagascar ( 19 ), Malawi ( 17 , 18 , 30 ) and South Africa ( 31 ). Five of the articles came, respectively, from Central Africa, DR Congo ( 15 , 16 ) and Cameroon ( 17 19 ); and West Africa, Cote d’Ivoire ( 16 , 19 ), Ghana ( 17 , 18 , 20 , 21 ), Burkina Faso, Mali, Senegal ( 19 ) and Nigeria ( 22 , 23 , 29 ) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Only 2 out of 17 articles included ( 15 , 20 ) reported both the average total cost, the direct cost and the indirect cost. Childhood cancer treatment costs were reported for lymphoma ( n = 9), multiple cancers ( n = 8), Wilms tumors ( n = 5), leukemia ( n = 4), retinoblastoma ( n = 3), nephroblastoma ( n = 1) and rhabdomyosarcoma ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high prevalence of caregiver burden in SSA including Ghana, not much is known regarding the association between caregiver burden and health-related quality of life among informal caregivers of older adults. The existing research has focused on family caregivers with schizophrenic patients [ 29 ], informal caregiving for children with lymphoma [ 30 ] and caregivers of stroke survivors [ 31 ]. For instance, Opoku-Boateng et al [ 29 ] wrote on economic cost and quality of life among family caregivers of schizophrenic patients attending psychiatric hospitals in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…Their study reports that caregivers with higher severity of depression, anxiety and stress experience higher caregiver burden and lower quality of life. Another independent study by Dawson et al [ 30 ] focused on costs, burden and quality of life associated with informal caregiving for children with lymphoma attending a tertiary hospital in Ghana. They found that lymphoma is linked to increased cost and higher burden impacting on quality of life among caregivers.…”
Section: Introductionmentioning
confidence: 99%